The Notched-frons Katydids of Taiwan (Orthoptera: Tettigoniidae: Conocephalinae: Copiphorini): redescriptions and keys for identification - Sri-In, Chalida; Yang, Jeng-Tze (Zootaxa, 2019)
The tribe Copiphorini is one of four tribes in the subfamily Conocephalinae (Orthoptera: Tettigoniidae). It is easily distinguished from other Tettigoniids by the markedly slanting head shape and the notched frons. This study revises the tribe in Taiwan. The specimens, which were examined for this study, were collected in Taiwan from October 1962 to May 2008 and deposited in the Museum of National Chung Hsing University and National Museum of Natural Science. There are five genera and six species distributed in Taiwan such as Euconocephalus nasutus (Thunberg, 1815), Euconocephalus pallidus (Redtenbacher, 1891), Pseudorhynchus gigas Redtenbacher, 1891, Pyrgocorypha formosana Matsumura & Shiraki 1908, Ruspolia lineosa (Walker, 1869), and Xestophrys horvathi Bolivar, 1905. These are redescribed and a key is provided to the genera and species from Taiwan. Notes are given on the habitats and distribution of the species.